2016
DOI: 10.1118/1.4940355
|View full text |Cite
|
Sign up to set email alerts
|

A combined time‐of‐flight and depth‐of‐interaction detector for total‐body positron emission tomography

Abstract: Purpose: In support of a project to build a total-body PET scanner with an axial field-of-view of 2 m, the authors are developing simple, cost-effective block detectors with combined time-of-flight (TOF) and depth-of-interaction (DOI) capabilities. Methods: This work focuses on investigating the potential of phosphor-coated crystals with conventional PMT-based block detector readout to provide DOI information while preserving timing resolution. The authors explored a variety of phosphor-coating configurations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…This relatively small increase in scatter fraction for larger acceptance angles may appear somewhat counterintuitive since oblique sinograms contain higher numbers of scatter events (35); however, the number of additional sinograms diminishes with increasing acceptance angle and so the overall scatter fraction is minimally affected by increasing acceptance angle, as demonstrated previously in simulations (10,35). Lastly, we measured the effect of the acceptance angle on spatial resolution by imaging a point source in a warm background, as it has been suggested that parallax error from depthof-interaction effects and blurring from photon noncollinearity may increase in a scanner with a wide acceptance angle, leading to degraded axial spatial resolution (7,36). However, there was only minor degradation in axial spatial resolution (0.5 mm in full width at half maximum) at a 46°acceptance angle, compared with a 14°a cceptance angle, in agreement with the simulation results shown by Schmall et al (7).…”
Section: Discussionmentioning
confidence: 64%
“…This relatively small increase in scatter fraction for larger acceptance angles may appear somewhat counterintuitive since oblique sinograms contain higher numbers of scatter events (35); however, the number of additional sinograms diminishes with increasing acceptance angle and so the overall scatter fraction is minimally affected by increasing acceptance angle, as demonstrated previously in simulations (10,35). Lastly, we measured the effect of the acceptance angle on spatial resolution by imaging a point source in a warm background, as it has been suggested that parallax error from depthof-interaction effects and blurring from photon noncollinearity may increase in a scanner with a wide acceptance angle, leading to degraded axial spatial resolution (7,36). However, there was only minor degradation in axial spatial resolution (0.5 mm in full width at half maximum) at a 46°acceptance angle, compared with a 14°a cceptance angle, in agreement with the simulation results shown by Schmall et al (7).…”
Section: Discussionmentioning
confidence: 64%
“…To fully exploit the sensitivity gains of extended axial length, and greater solid angle coverage, the axial acceptance angle will be large and cause a parallax error in the axial direction (a fully-3D 2 m long scanner with a 85 cm diameter will have an axial acceptance angle ±67°). This parallax error will be most pronounced in the center of the axial and transverse imaging FOV, and in addition to an inherent radial parallax error associated with the ring geometry, it has been suggested that PET scanner designs with long-axial FOVs may have worse spatial resolution compared to more traditional scanner designs having a shorter axial FOV (Berg et al 2016, Zhang et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Better configurations for TOF applications have been studied by several groups using a LaBr 3 /CeBr 3 pair (Schmall et al 2015) or an L 0.95 GSO-fast (0.025 mol% Ce)/L 0.95 GSO-slow (0.75 mol% Ce) pair (Yamamoto et al 2016). Another possible approach is the use of a phosphor-coated single layer crystal to make the depth-dependent decay time different (Berg et al 2016). Future work should therefore include a DOI detector using the fast and bright scintillator pair to construct the DOI-TOF block.…”
Section: Discussionmentioning
confidence: 99%